WATER LEAKED ANALYSIS IN THE GAS AIR HEATER IN PT CIREBON POWER SERVICE - Elli Prastyo; Syamsul Ma'arif (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2020)
PT. Cirebon Power Services is the first steam power plant (PLTU) in Indonesia that uses Supercritical Boiler technology. Combustion in a boiler using coal fuel produces hot gas which must be disposed of by utilizing a vacuum from the ID Fan and releasing it into the atmosphere. Gas Air Heater is a device that utilizes convection heat transfer from boiler exhaust heat to heat Primary Air and Secondary Air. The analysis was carried out by comparing the Gas Air Heater A and B through three parameters namely Air Leakage, X Ratio, and Efficiency. Data was collected from 31 December 2019 to 30 January 2020. The efficiency value of Gas Air Heater A was obtained 66% - 68% and Gas Air Heater B was 62% - 64%. The value of Air Leakage Gas Air Heater A is obtained 6% - 9% and Gas Air Heater B 10% - 12%. The value of X Ratio of Gas Air Heater A is 0.74 to 0.77, greater than Gas Air Heater B 0.68% to 0.71%.